A Modified Fixed Phase Iterative Recovery Algorithm for Restoration of Gray-Scale Blurred Images - Abdul-Jabbar, Jassim M. (Basrah Journal for Engineering Sciences, 2009)
A novel iterative method for the restoration of gray-scale blurred images is presented. The method is an enhanced modification of the Fixed-Phase Iterative Algorithm (FPIA). A blurred image is enhanced by Laplace operator during the FPIA method on each iteration. This modification is originally supported theoretically by a derivation of some iterative deblurring methods that are based on the enhanced version of the blurred image instead of the blurred image itself only. The modified fixed phase iterative algorithm (MFPIA) method is examined to restore some Gaussian-and motion-blurred gray-scale images. The restored Images via this proposed method are compared with the original FPIA method. From the comparison, it is apparent that the MFPIA method is better from human visual measurements point of view with less number of iterations. In addition to that benefit the restoration by the FPIA method results in images of bad quality even with high number of iterations.